Investigating the microstructural and electrochemical performance of novel La0.3Ba0.7Zr0.5X0.3Y0.2 (X = Gd, Mn, Ce) electrolytes at intermediate temperature SOFCs. Issue 23 (7th November 2022) - Irshad, Muneeb; Kousar, Naila; Hanif, Muhammad Bilal; Tabish, Asif Nadeem; Ghaffar, Abdul; Rafique, Muhammad; Siraj, Khurram; Aslam, Zeeshan; Assiri, Mohammed A.; Imran, Muhammad; Mosiałek, Michał; Zmrhalova, Zuzana; et al.
Abstract : La0.3 Ba0.7 Zr0.5 X0.3 Y0.2 (X = Gd, Mn, Ce named as LaBaZrGdY, LaBaZrMnY, and LaBaZrCeY, respectively) SOFC electrolytes were prepared via novel organic and chemical auto-combustion methods, via spinach extract and oxalic acid as chelating agents. Abstract : Here, for the first time, La0.3 Ba0.7 Zr0.5 X0.3 Y0.2 (LaBaZrXY; X = Gd, Mn, Ce named as LaBaZrGdY, LaBaZrMnY, and LaBaZrCeY, respectively) SOFC electrolytes were prepared via novel organic and chemical auto-combustion methods, respectively, using spinach extract (green) and oxalic acid as chelating agents. The effect of dopants and different chelating agents on the characteristics of synthesized LaBaZrXY electrolytes was investigated in detail. XRD confirmed the perovskite structure of LaBaZrGdY, LaBaZrMnY, and LaBaZrCeY. FESEM micrographs confirmed dense microstructures for all synthesized materials at 1150 °C. Prominent crystal growth and densification were observed for LBZCeY synthesized with oxalic acid. FTIR confirmed the presence of functional groups related to perovskite materials. The highest conductivity of 0.21 S cm −1 and 0.18 S cm −1 was observed for LBZCeY synthesized by both methods. The electrochemical performance of LBZCeY prepared with spinach extract, and oxalic acid yielded a maximum power density of 0.35 W cm −2 and 0.61 W cm −2 at 600 °C, respectively. LBZCeY synthesized has the potential for use as an intermediate temperature SOFC electrolyte. The current investigation suggests that LaBaZrXY can be successfully prepared using organic combustion with spinach extract paving the way for green synthesis of perovskites with minimal impact on the environment.